Migration Museums: A Proposed Typology - Petelska, Michalina (Muzeológia a Kultúrne Dedičstvo, 2022)
The aim of this article is to propose the perception of migration museums as a coherent group. Migration museums are perceived by some professionals as specialised, thematic historical or ethnographic museums, whereas this paper organises the diversity of historical and contemporary migratory movements in connection with the current dynamic development of museums. Among the migration museums, the following types were grouped and distinguished: migration museums which comprehensively address the subject of various migrations, migration museums in the historical migration infrastructure, open-air migration museums, migration museums dedicated to specific events, migration museums established by immigrant communities and virtual migration museums. The importance of addressing the topic of migration in other types of museums, such as maritime, ethnographic, historical and art museums, is also highlighted. Covering the global network of migration museums allows us to search for answers to the question of the role of museums at a time when refugees and climate migrations will be among the greatest challenges for humanity.